Green chemistry Green synthesis and physicochemical characterization of Cu(II) and Ni(II) Schiff base complexes derived from 2,3-dihydroxybenzaldehyde (مجلة البحوث الأكاديمية, 2026)
Green chemistry, which focuses on the creation of ecologically friendly synthetic techniques, has emerged as a crucial strategy in contemporary coordination chemistry. This study used sustainable methods to manufacture Schiff base ligands from aminopyridine derivatives and 2,3-dihydroxybenzaldehyde. Their copper(II) and nickel(II) complexes were then made using green synthetic methods that minimized the use of solvents and energy, such as mechanochemical grinding and microwave-assisted synthesis.Using a variety of physicochemical and spectroscopic methods, including elemental analysis, Fourier-transform infrared spectroscopy (FT-IR), Mass spectrum, magnetic susceptibility measurements, molar conductivity, and thermal analysis, the synthesized metal complexes were isolated in high yields. Spectral measurements demonstrated chelation behavior by confirming the interaction of the Schiff base ligands to the metal centers via the azomethine nitrogen and phenolic oxygen atoms.